Foreign Language Learning In The Modern Era According To The Prophet's Hadith - Al Khoiron, Muhamad Fiqhussunnah; Muna, Faizul; Putri, Yulita; Nurhuda, Abid; Lathif, Nur Muhammad (Program Studi Magister Pendidikan Bahasa Indonesia FKIP Universitas Mataram, 2024)
In the context of the modern era which is characterized by technological advances and the phenomenon of globalization, the ability to communicate in various foreign languages is becoming increasingly crucial. Parallel to the period in the life of Rasulullah SAW, where the importance of understanding foreign languages was expressed through the central role of Zaid bin Thabit as a translator. This research aims to provide an in-depth understanding of the significance of studying foreign languages in the modern era according to the hadith of the Prophet. The method used is qualitative with a literature study approach model and then concluded descriptively. The research results show that learning foreign languages in the modern era according to the hadith of the Prophet is very important because it is used to interact with anyone without borders, even in different countries. Apart from that, learning foreign languages in this modern era is very easy and affordable due to the emergence of various platforms such as mobile learning applications, online video conversation platforms, and online resources. So with that, a person can fulfill their need to interact without limits, however, there needs to be something called supervision so that undesirable things don't happen, such as accessing foreign language content that is not age-appropriate, the displacement of Indonesian or regional languages and the loss of local cultural values.